Effect of Dividend Declaration on Stock Price Movement in Bangladesh – A Study on Five Selected Private Commercial Banks Listed in DSE - Jahan, Nasrin (Asian Accounting and Auditing Advancement, 2019)
Payments of dividends are the key return variable from which investors determine share value. They represent a source of cash flow to the stockholders and provide information about the firms’ current and future performance. Investors mostly look at the profitability of the firm while purchasing equity shares from the secondary market. Since the dividend is paid to the shareholders is one of the best indicators of profitability. It is generally believed that dividend plays a crucial role in determining the market price of the share. The relationship between dividend declaration and share price is not clear in the literature on finance and it is still a controversial issue in both developing and under-developing countries. This research attempts to analyze the behavior of stock price reactions to the declaration of dividends of five commercial banks operating in Bangladesh. This research basically focuses on secondary data obtained from the Dhaka stock exchange. This is qualitative research because it is designed to tell the researcher how and why share price moves after dividend declaration dates. This study also analyzed the commercial banks’ dividend practices with two existing theories of dividend policies named Modigliani and Miller hypothesis of irrelevance and relevance to Gordon’s model. It appears that Gordon’s model can best describe the commercial bank's dividend practices. The major objective of this study is to identify whether a dividend declaration conveys any information to the market that results in a price reaction for adjusting the dividend announcement information. Finally, the dividend announcement has no contribution to conveying information to the market that results from price reaction.